Perceived Safety and Security Concerns among Tourists in Thamel-A Tourism Hub in Kathmandu Valley, Nepal - Arun Kumar Sharma; Birendra KC; Araceli Hernandez Calderon (Lasigo Akademia Indonesia, 2020)
The safety and security of a destination is an essential factor that helps travelers decide whether to visit or not. In Nepal, Thamel is the main destination for tourists due to the availability of multiple facilities and services. In fact, most of the tourists who use airspace to travel to Nepal, start and conclude their journey in Thamel. Therefore, the safety and security of Thamel is an important factor that influences the fate of the Nepalese tourism industry. However, there is a lack of research to understand the safety and security situation of Thamel. The purpose of this exploratory study is to assess the overall security situation and challenges in Thamel. Descriptive statistics are used to present the findings. Findings suggest that Thamel as a tourism destination has many areas for improvement to provide better tourist experiences. Since Thamel is a starting and concluding point of attraction for tourists, we offer important managerial implications and future research directions.